Removal of Cr(VI) from the soil containing nitrate by using electrokinetic treatment - maryam mosavikia; Ali Shahidi; Abbas KhasheiSiuki; mohammad hassan sayari (رویکردهای نوین در مهندسی آب و محیط زیست)
Objective: Due to the toxicity of metals, their side effects may cause serious damage to soil organisms, plants and living organisms. Many conventional methods for cleaning pollution from soil have problems and limitations. The electro kinetic method is a relatively new method for remediating soils contaminated with heavy metals, which has a high efficiency in removing heavy metals from the soil compared to other existing methods.Methods: In this research, the removal of chromium (VI) from nitrate-containing soil has been investigated. At first, the soil was artificially contaminated with potassium dichromate at a concentration of 250 mg/kg, and then in order to investigate the effect of nitrate on the removal of chromium. The soil was also impregnated with calcium nitrate.Results: By conducting electrokinetic experiments, it was found that with the increase of the electric current introduced into the soil, the electric gradient passing between the electrodes increased, as a result of which the transfer of ions also increased under the influence of the phenomenon of ion migration and electroosmosis. The percentage gives 98.28%. Also, the use of EDTA complexing agent compared to distilled water increases the efficiency of the method from 95.57% to 97.80%. As a result, the use of EDTA electrolyte and increasing the voltage increases the removal efficiency.Conclusions: Results revealed experiments showed that the use of the electrokinetic method has a negligible effect on the removal of chromium (VI) from soil containing nitrate.